Application of modified affine theorem to orthotropic rectangular reinforced concrete slab with interior corner opening parallel to shorter side - Manasa, D.; Rambabu, K.; Durgarani, K. (Journal of Structural Engineering, 2024)
An attempt has been made to apply modified affinity theorem to determine collapse load of two-way orthotropic slab with interior corner opening parallel to shorter side. Keeping in view the basic principles of yield line theory, all possible admissible yield line patterns are considered for the given configuration of the slab subjected to uniformly distributed load (udl). A computer program has been developed to solve the virtual work equations for the admissible yield line failure patterns of the slab for different given data. Illustration of above methodology has been brought out with numerical examples. Relevant tables and charts for given data and the governing admissible failure patterns of the slab for different openings are presented.